Jessica Randolph Smith papers - Smith, Jessica Randolph
Family memoir by Smith; article on the origin of the Confederate flag presented at the 1915 annual conference of the United Daughters of the Confederacy, together with Smith's notes on the article; and newspaper clipping.
Resident of Henderson, N.C.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Smith family; United Daughters of the Confederacy; Flags -- Confederate States of America